2014
DOI: 10.1093/rheumatology/ket460
|View full text |Cite
|
Sign up to set email alerts
|

International periodic fever, aphthous stomatitis, pharyngitis, cervical adenitis syndrome cohort: description of distinct phenotypes in 301 patients

Abstract: We describe the largest cohort of PFAPA patients presented so far. We confirm that PFAPA may present with varied clinical manifestations and we show the limitations of the commonly used diagnostic criteria. Based on detailed analysis of this cohort, a consensus definition of PFAPA with better-defined criteria should be proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
141
1
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(176 citation statements)
references
References 21 publications
16
141
1
18
Order By: Relevance
“…However, such patients have been reported in other studies and respond promptly to steroids and tonsillectomy, treatments used in PFAPA. 4,5,20,21 Fourth, genetic testing was not obtained in all PFAPA patients to rule out monogenic periodic fever syndromes, but most participants were followed up for several years and did not develop symptoms concerning for monogenic syndromes.…”
Section: Figure 1 Continuedmentioning
confidence: 99%
“…However, such patients have been reported in other studies and respond promptly to steroids and tonsillectomy, treatments used in PFAPA. 4,5,20,21 Fourth, genetic testing was not obtained in all PFAPA patients to rule out monogenic periodic fever syndromes, but most participants were followed up for several years and did not develop symptoms concerning for monogenic syndromes.…”
Section: Figure 1 Continuedmentioning
confidence: 99%
“…Pharyngitis is seen in 65-100%, cervical adenitis in 61-100%, aphthous stomatitis in 38-71% (5). In addition, some patients may have headache, abdominal pain, diarrhea, joint aches, chills and redness in the body (5). Although antipyretics may provide benefit from time to time, antibiotics or anti-inflammatory drugs do not provide any benefit (2).…”
Section: Discussionmentioning
confidence: 99%
“…Stojanov et al (10) suggest the concept of T-cell proliferation raised by activation of immune system established on a genetic basis after a microbial trigger in pathogenesis of PFAPA. Patients who underwent tonsillectomy had no histopathologically significant pathology other than chronic inflammation (2,5).…”
Section: Discussionmentioning
confidence: 99%
“…In a multicentre cohort analysis by Hofer et al (16), 301 patients with PFAPA were evaluated and clinical manifestations were reported. The study results reported so far are presented in Table I (2,8,(17)(18)(19)(20)(21).…”
Section: Clinical Findingsmentioning
confidence: 99%
“…The average number of attacks is 11.5 per year (2,14). Aphthous ulcer is frequently seen on the lips and in buccal mucosa, accompanied by fever attacks in 40-70% of cases, and heals without scarring (2,16,17). Pharyngitis is detected in 90% of the patients.…”
Section: Clinical Findingsmentioning
confidence: 99%